Sosialisasi Pembuatan Sabun Cuci Piring Sederhana Kepada Ibu Rumah Tangga Di Desa Padang Tualag Kecamatan Langkat - Nurul Hasanah Syah; Novya Nadilla; Siswanto Siswanto (Maslahah: Jurnal Pengabdian Masyarakat, 2021)
In the current pandemic, many complaints are received by the public. Not escape from the difficulty of finding income. One of them is to meet the needs of the kitchen and other household needs. Dish soap is a daily necessity for housewives. Making dish soap can also be done by individuals to reduce daily competition, because it can be done using chemicals that are cheap and easy to find. Therefore, outreach activities to housewives in the village of Padang Tualang, Langkat aim as an effort to increase the economic independence of housewives in the area. The method used for this community service activity is through direct demonstrations in front of the participating mothers. A total of 30 participants were enthusiastic in participating in activities ranging from participating in making basic materials, providing the equipment needed to the final process, namely packaging. In addition, it must also be studied from the safety aspect of the chemicals used and also the calculation of the capital to make these materials.